Tingkat Partisipasi Masyarakat dalam Mitigasi Bencana di Kawasan Rawan Bencana Gunung Marapi di Nagari Batu Palano Kecamatan Sungai Pua Kabupaten Agam - Yudistira, Yudistira; Chandra, Deded (Lembaga Yasin AlSys, 2025)
This study aims to analyze community participation in disaster mitigation and identify the supporting and inhibiting factors influencing community involvement in Nagari Batu Palano, Sungai Pua District, Agam Regency. A mixed-methods approach was used, with quantitative questionnaires to measure participation levels and qualitative interviews to explore influencing factors in depth. The results show that community participation in Mount Marapi disaster mitigation remains low, with a participation index of 51.52%. Awareness and active involvement in training and evacuation simulations are not yet optimal. Inhibiting factors include the lack of mitigation activities organized by the government and the absence of evacuation route maps. Conversely, supporting factors for participation are the community's good understanding of the importance of mitigation. This study provides a comprehensive overview of the challenges and potential in enhancing community preparedness for Mount Marapi disasters.